Description of a new genus of Elaphidiini with two new species (Coleoptera, Cerambycidae, Cerambycinae) - Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2017)
Elaphidiini Thomson, 1864 is a large tribe of Cerambycidae composed of 92 genera with species distributed from Canada to southern South America. Lingafelter (1998) performed a generic level phylogenetic analysis of the tribe and provided a key to the known genera. According to Lingafelter, Elaphidiini is characterized as follows: mesally-spined antenna (lost in some taxa), narrow metepisternum with a centrally positioned keel, strongly sclerotized below and membranous above; prosternal process between procoxae slightly to strongly expanded at apex (rarely linear and unexpanded); terminal palpomeres much wider at apex than base; and coarsely faceted eyes (with few exceptions).